The Background Structure of Entrepreneurial Team and Strategic Investment Decisions: A Collective Psychological Capital Perspective - Guo, Li Xin; Lu, Kun-Hwa; Cheng, Ya-Fang; Liu, Chi-Fang (Frontiers in Psychology, 2019)
Drawing from the perspective of collective psychological capital, this study analyzes the internal mechanism of how top management structure influences R&D and marketing investment decisions. Utilizing a sample of 346 Chinese listed companies in high-tech industries from 2012 to 2017, we examine the relationship between the proportion of entrepreneurial team with technology/marketing-related background and R&D/marketing expenditure. The empirical results show the proportion of entrepreneurial team with the technological background is positively related to R&D expenditure and negatively related to marketing expenditure. On the contrary, we also find that the proportion of entrepreneurial team with a marketing background is a negative correlation with R&D expenditure and positive correlation with marketing expenditure. Our study has expanded the perspective and scope of the research on the antecedents of strategic investment decisions, and the practical implications are discussed.